Alterações biomecânicas e de sensibilidade à dor relacionadas ao encurtamento da cápsula posterior do ombro – Avaliação e tratamento - Rosa, Dayana Patricia (Universidade Federal de São Carlos, 2017)
Some studies have shown that posterior capsule tightness may be related to shoulder dysfunctions and alterations in range of motion. However, there is no consensus in literature about how to specifically assess posterior capsule tightness, considering that bony adaptions, as humeral retroversion, may influence the clinical measurements suggested in previous studies. Furthermore, few studies have evaluated the effect of interventions on the posterior capsule tightness. In addition, the low quality of the studies limits the clinical decision-making. The aims of this thesis were: 1) to assess scapular and humeral kinematics, shoulder range of motion and external rotators strength, pressure pain threshold, pain and function in individuals with posterior capsule tightness with and without shoulder pain; 2) to compare the effects of a specific and a non-specific intervention to posterior capsule tightness and pain in individuals with capsule tightness and shoulder pain on the same outcomes presented in aim 1; 3) to determine how the posterior capsule tightness and humeral retroversion interact and influence measurements used to measure shoulder range of motion in the clinical practice. The posterior capsule tightness was quantified by the Low Flexion test. The humeral retroversion was quantified using the bicipital forearm angle. The electromagnetic system was used to measure kinematics. Digital inclinometer, dynamometer and goniometer were used to assess range of motion, muscle strength and pressure pain threshold, respectively. The Shoulder Pain and Disabilities Index (SPADI) assessed shoulder pain and function. In general, the results showed that individuals with shoulder pain presented changes in scapular and humeral kinematics and in shoulder range of motion, which were not intensified with posterior capsule tightness. However, the capsule tightness associated to shoulder pain contributed to worse pain and function of the shoulder, and decreased pressure pain threshold, which suggest increased pain sensitivity. After 4 weeks of intervention, only the specific one decreased the posterior capsule tightness. Both protocols decreased the humeral translations, shoulder pain and increased shoulder range of motion and pressure pain threshold. The posterior capsule tightness and humeral retroversion influenced the clinical measurements, but the two combined condition showed greater shoulder range of motion deficit. Thus, it is believed that individuals with the same musculoskeletal dysfunction, as shoulder pain, may respond differently to pain and develop individual adaptations to avoid pain and to preserve function. Further investigation of the clinical measurements used in the present study is needed in individuals with shoulder dysfunction.
Biomechanical and pain sensitivity changes related to posterior capsule tightness - Evaluation and treatment
Keywords: Alongamento; Dor; Escápula; Manguito rotador; Mobilização; Retroversão; Mobilization; Pain; Retroversion; Rotator cuff; Scapula; Stretching; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL